Frequency of post operative complications after functional and selective next dissection in patients with squamous cell carcinoma oral cavity - TANNAZA QAYYUM, ASHFAQ-UR-RAHIM, SADIQ ALI, MUHAMMAD NAUMAN, ALI ABU BAKAR, UROOJ KIRMANI, NAVAIRA TARIQ, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Regarding those afflicted with cancer of the head and neck who have cervical neck metastases, neck dissection is a surgical treatment. In order to maximize the cancer's cure rate, neck dissection aims to establish loco-regional control. This procedure may result in a number of problems. Objective: To find the frequency of post-operative complications after neck dissection in patients with confirmed diagnosis of squamous cell carcinoma of oral cavity. Study Design: Prospective interventional study. Place and duration of study: Faryal Dental College's Department of Oral and Maxillofacial Surgery, Lahore from 8th March 2022 to 8th September 2022. Methodology: One hundred and twenty three patients who were eligible to participate were enrolled. Functional and selective neck dissection was carried. Complications were noted at 30th post-operative day. Results: The mean age of the 123 patients was 42.40±10.95 years, with 28.5% (n=35) being between the ages of 18 and 35 and 71.5% (n=88) being between the ages of 36 and 65. There were 47.2% (n=58) females and 52.8% (n=65) men. Frequency of wound dehiscence, marginal mandibular nerve weakness and accessory nerve weakness was 11.14%, 8.9% and 9.8% respectively. Conclusion: After neck dissection, a number of problems might arise. The likelihood of problems after this operation might be reduced by being aware of these potential issues. Keywords: Neck dissertation, Squamous cell carcinoma, Wound dehiscence. Background: Regarding those afflicted with cancer of the head and neck who have cervical neck metastases, neck dissection is a surgical treatment. In order to maximize the cancer's cure rate, neck dissection aims to establish loco-regional control. This procedure may result in a number of problems. Objective: To find the frequency of post-operative complications after neck dissection in patients with confirmed diagnosis of squamous cell carcinoma of oral cavity. Study Design: Prospective interventional study. Place and duration of study: Faryal Dental College's Department of Oral and Maxillofacial Surgery, Lahore from 8th March 2022 to 8th September 2022. Methodology: One hundred and twenty three patients who were eligible to participate were enrolled. Functional and selective neck dissection was carried. Complications were noted at 30th post-operative day. Results: The mean age of the 123 patients was 42.40±10.95 years, with 28.5% (n=35) being between the ages of 18 and 35 and 71.5% (n=88) being between the ages of 36 and 65. There were 47.2% (n=58) females and 52.8% (n=65) men. Frequency of wound dehiscence, marginal mandibular nerve weakness and accessory nerve weakness was 11.14%, 8.9% and 9.8% respectively. Conclusion: After neck dissection, a number of problems might arise. The likelihood of problems after this operation might be reduced by being aware of these potential issues. Keywords: Neck dissertation, Squamous cell carcinoma, Wound dehiscence.